RIGHTS OF THE CHILD WITH FUNCTIONAL DIVERSITY - Low, Sandra Trindade; Spinelli , Maria Benita Alves da Silva; Marques , Carlos Reinaldo Carneiro; Santos , Adrielli Maria Sales; Beserra , Maria Aparecida; da Silva , Samara Cecília Sabino Pereira; Chaves, Marco Vinícius Beserra; Neta , Maria Joana Pereira (Seven Editora, 2024)
Objective: To describe relevant aspects of the rights of children with functional diversity. Methodology: This is a descriptive, exploratory, cross-sectional study with a quantitative approach and the purpose of evaluating the rights of 95 children with functional diversity in an outpatient clinic of a public health institution. The research was approved by the UPE Research Ethics Committee opinion number: 2.753.756 and CAAE 67017117.8.0000.5192, part of the information came from those responsible, after the application of TALE/TCLE in compliance with resolution CNS 466/12. The data were descriptively analyzed through absolute and percentage frequencies. To evaluate the association between two categorical variables, Pearson's Chi-square test or Fisher's exact test were used when the condition for using the Chi-square test was not verified. Results: It was seen that most children were having access to health, education, leisure and quality housing, however there are still children with different realities facing difficulties to guarantee these rights, especially low-income children. Conclusion: Although children are having rights, health care had a low percentage of children being monitored at the Basic Health Unit through childcare. DOI:https://doi.org/10.56238/sevened2024.037-071